16S rDNA‐based metagenomic analysis of dental plaque and lung bacteria in patients with severe acute exacerbations of chronic obstructive pulmonary disease. (1st February 2014) - Tan, L.; Wang, H.; Li, C.; Pan, Y.
<x xml:space="preserve">Abstract</x> Background and Objective Acute exacerbations of chronic obstructive pulmonary disease (AE‐COPD) are leading causes of mortality in hospital intensive care units. We sought to determine whether dental plaque biofilms might harbor pathogenic bacteria that can eventually cause lung infections in patients with severe AE‐COPD. Material and Methods Paired samples of subgingival plaque biofilm and tracheal aspirate were collected from 53 patients with severe AE‐COPD. Total bacterial DNA was extracted from each sample individually for polymerase chain reaction amplification and/or generation of bacterial 16S rDNA sequences and cDNA libraries. We used a metagenomic approach, based on bacterial 16S rDNA sequences, to compare the distribution of species present in dental plaque and lung. Results Analysis of 1060 sequences (20 clones per patient) revealed a wide range of aerobic, anaerobic, pathogenic, opportunistic, novel and uncultivable bacterial species. Species indistinguishable between the paired subgingival plaque and tracheal aspirate samples (97–100% similarity in 16S rDNA sequence) were dental plaque pathogens (Aggregatibacter actinomycetemcomitans, Capnocytophaga sputigena, Porphyromonas gingivalis, Tannerella forsythia and Treponema denticola) and lung pathogens (Acinetobacter baumannii, Klebsiella pneumoniae, Pseudomonas aeruginosa and Streptococcus pneumoniae). Real‐time polymerase chain reaction of 16S rDNA indicated lower levels of Pseudomonas aeruginosa and Porphyromonas gingivalis colonizing the dental plaques compared with the paired tracheal aspirate samples. Conclusion These results support the hypothesis that dental bacteria may contribute to the pathology of severe AE‐COPD.